Improving Supply Chain and logistics and reducing costs by design and improvement of packaging with the help of Lean and DFL : Project-based case study - Mikkola, Antti (My University, 2021)
Logistics is critical part of supply chain, due to enabling efficient and reliable value-creating operations, with the potential to increase sales and profits. Main goals of the case study are to improve product transport packaging, packaging process, packaging and transportation costs and all related material flows throughout the supply chain in the case company. This is done by analyzing current state and employing rarely used Design for Logistics (DFL) theory framework, combined with Lean, to form a ground up approach for optimizing the supply chain. Empirical study is carried out as case study research utilizing inductive case study framework, action research cycles and mixed methods. Both deductive and inductive reasoning are used. Theories have been employed and tested in practice, but new case related theory has also been made from ground-up based on data, experimentation, observation, and analyses. 3D-modeling is utilized extensively. Case results include various findings regarding current state of logistics processes, costs and their relationship between packaging and packaging processes in the case company. Results also include creating a modular, interchangeable transport packaging for upcoming new product families, creating new material flow processes throughout supply chain, overhauling packaging process and creating a semi-automated packaging cell. Other resulting outcomes include e.g., significantly lower production costs, process variance and time, and transportation costs, together with increased economies of scale as well as flexibility and availability regarding transportation options. Results also point theory-wise the potential and significance of packaging for the whole supply chain entity as a creator of increased value and efficiencies, especially by facilitating and enabling creation of new capabilities regarding various internal and external processes and related production technologies. Results of the study are both valid and reliable due to the methodology used, where de facto continuous validity and reliability evaluation was built-in because of periodical group reviews and other events partaken by cross-functional team of professionals. Results have been realized by utilizing various, both alternative and supplementary research methods. Findings and results have been further verified by prototyping, various in-practice testing, 3D-modeling as well as by ongoing implementation and commissioning to the case company’s operations. Further research could include how to systemically introduce and implement DFL into use as integral part of product and production development alongside other DFX tools.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management